Analisis Budaya Organisasi, Kompensasi, Dan Disiplin Kerja Terhadap Organizational Citizenship Behavior (OCB) Melalui Motivasi Sebagai Variabel Moderasi - Suseno; Kirana, Kusuma Chandra; Lukitaningsih, Ambar (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2021)
This research purported to discover the influence of corporate culture, compensation and working discipline on Organizational Citizenship Behavior (OCN) using motivation as moderating variable. Research population covered all employees in PERUMDAM Bantul having permanent officer status as many 115 persons. Research sampling was based on Slovin method resulting in 90 people selected using random sampling technique. Research method was based on quantitative approach. The research utilized SmartPLS 3.2.8 to conduct inferential analysis. Based on the result of inferential analysis using SmartPLS 3.2.8 it can be concluded that there was tangible influence of corporate culture, compensation and working discipline on Organizational Citizenship Behavior (OCN) using motivation as moderating variable.The result of this research is applicable as reference to improve OCB in any companies simply by strengthening corporate culture, rationalizing compensation, maintaining workplace discipline and motivating the employees to work even harder.